Acute abdomen with intraperitoneal free gas: a diagnostic pitfall of pneumatosis cystoides intestinalis—a case report - Hao Wang; Yan-Hui Yang (Frontiers in Medicine, 2025)
BackgroundPneumatosis cystoides intestinalis (PCI) is a rare condition characterized by the presence of multiple gas-filled cysts located beneath the intestinal submucosa or plasma membrane. The pathogenesis of PCI remains incompletely understood, and its clinical presentation lacks specificity.Case descriptionA 69-year-old woman was admitted to the hospital with symptoms of abdominal distension, abdominal pain lasting over 2 weeks, and altered consciousness for 3 days. She had a two-year history of mixed connective tissue disease and was undergoing regular hormone therapy. Upon admission, she demonstrated signs of peritoneal irritation, and computed tomography (CT) revealed the presence of multiple free air pockets within the abdominal cavity, as well as “bead-like” translucent areas within the intestinal wall. An emergency abdominal exploration revealed extensive gas accumulation in the wall of the small intestine and multiple gas bubbles in the mesentery. Subsequently, resection and anastomosis of the affected intestinal section were performed. Postoperative pathology identified multiple non-endothelial cystic cavities within the submucosa and muscularis propria of this segment of the small intestine, with Escherichia coli and Phocaeicola vulgatus detected in the affected intestinal wall. The patient was further treated in the Intensive Care Unit (ICU) after surgery, but following a brief period of improvement, she developed a lung infection and unfortunately passed away.ConclusionThis case report demonstrates the diagnostic difficulties in patients with peritonitis with abdominal free gas in intestinal gas cysts, reveals the potential role of abnormal intestinal flora, especially the never reported colonization by Phocaeicola vulgatus, in the development of PCI combined with abdominal free gas.